Relationship between oxidative stress, glutathione S-transferase polymorphisms and hydroxyurea treatment in sickle cell anemia - Humberto Silva, Danilo Gruenig [UNESP]; Belini Junior, Edis [UNESP]; Torres, Lidiane de Souza [UNESP]; Ricci Junior, Octavio; Lobo, Clarisse de Castro; Bonini-Domingos, Claudia Regina [UNESP]; de Almeida, Eduardo Alves [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
This study evaluated the oxidative stress and antioxidant capacity markers in sickle cell anemia (SCA) patients with and without treatment with hydroxyurea. We assessed GSTT1, GSTM1 and GSTP1 polymorphisms in patients and a control group. The study groups were composed of 48 subjects without hemoglobinopathies and 28 SCA patients, 13 treated with HU [SCA (+ HU)], and 15 SCA patients not treated with HU [SCA (- HU)]. We observed a significant difference for GSTP1 polymorphisms in SCA patients with the V/V genotype that showed higher glutathione (GSH) and Trolox equivalent antioxidant capacity (TEAC) (p = 0.0445 and p = 0.0360), respectively, compared with the I/I genotype. HU use was associated with a 35.2% decrease in the lipid peroxidation levels of the SCA (+ HU) group (p<0.0001). Moreover, the SCA (+ HU) group showed higher TEAC as compared to the control group (p = 0.002). We did not find any significant difference in glutathione-S-transferase (GST) activity between the groups (p = 0.76), but the catalase (CAT) activity was about 17% and 30% decreased in the SCA (+ HU) and SCA (HU) groups, respectively (p<0.00001). Whereas the plasma GSH levels were similar to 2 times higher in the SCA patients than the control group (p = 0.0005). HU use has contributed to higher CAT activity and TEAC, and lower lipid peroxidation in patients under treatment. These findings may explain the influence of HU in ameliorating oxidative stress on SCA subjects. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Sickle cell anemia; Oxidative stress; Hydroxyurea; GST polymorphisms